A case of V180I genetic Creutzfeldt-Jakob disease presenting with conspicuous facial mimicry. Issue 1 (1st January 2019) - Iwasaki, Yasushi; Mori, Keiko; Ito, Masumi; Kawai, Yoshinari
ABSTRACT: Although there have been no reports of facial mimicry in patients with Creutzfeldt-Jakob disease (CJD), we encountered a patient with genetic CJD with prion protein gene codon 180 mutation (V180I gCJD) who apparently showed this interesting clinical finding. The patient was an 87-year-old Japanese woman, and the first observed CJD symptom was poor spontaneity. She gradually showed cognitive dysfunction and subsequently gait disturbance. A prion protein gene analysis revealed a V180I mutation with methionine homozygosity at codon 129. Facial mimicry was observed 7 months after disease onset and continued for approximately 9 months. Pathological laughing and startle reaction were also observed during approximately the same period, whereas myoclonus was observed at a later stage, 12 months after disease onset, and was very mild in degree. Electroencephalography studies showed a diffuse slow basic pattern without periodic sharp wave complexes. Diffusion-weighted magnetic resonance imaging showed extensive hyperintensity in the cerebral cortex, and there was also hyperintensity with edematous swelling in the same regions on T2-weighted and fluid-attenuated inversion recovery images. On the basis of the magnetic resonance imaging findings and the findings of previous case reports of V180I gCJD, we speculate that the characteristic extensive cerebrocortical involvement observed in V180I gCJD was implicated in the pathogenesis of the facial mimicry observed in this case.